Nonlinear Effects of Climate Change on Economic Growth in the MENA Region: Does Government Effectiveness Matter? - Namri, Taha; Saou, Mohamed; El Abbassi, Idriss (International Journal of Energy Economics and Policy, 2026)
This study investigates the nonlinear effects of climate change, expressed by temperatures and precipitation patterns, on economic output in the Middle East and North Africa (MENA) region. Using fixed effect panel models for 16 countries over the period 1990-2023, the analysis estimates the temperatures and precipitation thresholds and examines how those thresholds vary across geographic and institutional conditions. The results reveal a robust inverted U-shaped relationship between temperatures and GDP per capita, indicating that moderate warming may initially support economic activity, while higher temperature levels generate adverse growth effects. In contrast, precipitation exerts weak and mostly linear effects on output. Temperature thresholds are found to be higher in North Africa and countries with stronger governance, highlighting the role of institutions in mitigating climate-related economic damages. Overall, the findings point to substantial heterogeneity in climate growth relationships across the MENA region and emphasize that institutional capacity is a key determinant of climate resilience. These results underline the need for climate adaptation strategies that are not only country-specific but also grounded in improvement in governance and public policy effectiveness.